Analysis of performance indices for simulated skeleton descents - Gong, C.; Phillips, C. W. G.; Rogers, E.; Turnock, S. R. (Procedia Engineering, 2016)
In the winter Olympic sport of Skeleton, sliders sprint and load themselves onto the sled facing head forwards. The slider uses primarily their shoulders and torso to apply control to the direction of the sled as it progressively gains speed during its descent. These small control course keeping maneuvers alongside more severe use of toe tapping onto the ice will help determine the eventual trajectory of the sled. It is therefore of interest to consider for a possible trajectory what control actions will determine the fastest descent time and in particular what metrics should be examined. In this paper a three degree-of-freedom simulation has been developed to analyse the influence of different control strategies on the descent time of a bob-skeleton. A proportional-derivative (PD) controller is used to steer the simulation down a representation of the Igls ice-track. Parametric variations of the simulation's performance were analysed and compared to identify possible correlations for controllers assist the design of an optimal controller. Analysis of the results have identified positive correlations between descent time, transverse distance travelled and energy dissipation establishing that the fastest descent time is achieved by minimising the energy lost through the descent.